„Buch“, „hörbuch“, „e-book“ & co. Lexical change and lemma update of a german learner ́s dictionary portal - Hollós, Zita (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2025)
In the course of the digitalisation of everyday life and communication, traditional media such as books, letters, radio and television, to name but a few, are gradually fading into the background. The objects of our cultural epoch, that of the 20th century, are gradually being replaced by immaterial phenomena. Young people use these and also the words that describe them, such as Hörbuch, Audiobook, E-Book or E-Mail, Post, Like and various online or on-demand products on a daily basis and also in dealing with social media. What does this mean for the maintenance of a learner dictionary portal for German as a foreign language such as E-KOLLEX DAF? Which data needs to be updated first so that this resource continues to appeal to young people and remains up to date? Which dictionary portals and tools or corpus statistics can help lexicographers to update the lemma inventory, initially for the “Media” topic area? Answers to these questions are sought in the following article.